Journal Information and Editorial Board - Ab Gani, Muhamad Abdul Aziz (Idealogy Journal; Vol 3 No 1 (2018): Idealogy Journal (April 2018), 2018)
This section presented about the Journal Information, Editorial Board, Panel of Reviewer, Copyright Notice, and Committee of Publication Ethic. This information for further reference by the author for the official needs on their own career path.